Effect of Strengthening of Steel Beams with Variable Length by Using Carbon Fiber. (21st August 2019) - Al-Ridha, Ahmed S. D.; Atshan, Ali F.; Mahmoud, Kamal Sh.; Hameed, Qusai Kh.
Abstract : In this research, four steel beams were fabricated and tested to understand the influence of their strengthening (by using carbon fiber) with various span lengths on load deflection, load-strain, and ultimate load responses. All tested beams have the same cross-sectional area, and they are all strengthened by using intermediate stiffeners and cover steel plate at top flange to insure that failure will occur at the bottom flange. The tested steel beams are divided into two groups according to their clear span lengths 1400 and 1900 mm, and each group is subdivided into two beam cases based on whether they are strengthened by carbon fiber or not. From this study, it was found that the load deflection and load-strain curves for the beams strengthened by carbon fiber are stiffer than the original beams (without carbon fiber) with similar clear span lengths (this behavior was more obvious with smaller lengths). Moreover, the load deflection and load-strain responses have shown that beams became stiffer when the effective length is reduced (with and without carbon fiber), and this behavior was more apparent with the beams strengthened by carbon fiber. On the contrary, from the results of ultimate load of the beams, it can be concluded that the percentage of increase in ultimate load for the beam strengthened by carbon fiber is increased with the decrease in its span length. One could also conclude that when the effective length decreases, the ultimate load was increased and the percentage of this increasing is magnified with the presence of carbon fiber.